2001
DOI: 10.1207/s15327027hc1303_4
|View full text |Cite
|
Sign up to set email alerts
|

Participants' Perceptions of a Peer-Helper, Telephone-Based Social Support Intervention for Melanoma Patients

Abstract: This descriptive study investigated perceptions of a peer-helper, telephone-based, social support intervention for melanoma patients receiving immunotherapy. Participants were 59 male and female Stage 3 or4 melanoma patients (helpees) at a Comprehensive Cancer Center and 29 former patients (helpers). Helpers were matched with helpees about to begin immunotherapy based on the site of the melanoma, age, and, when possible, biological sex. The intervention consisted of 2 required telephone contacts initiated by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(11 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…However, printed material on the disease and treatment is scarce, particularly in the low-volume centers, indicating that an important aspect of patient care is underappreciated [34,35]. Most recurrences are detected by the patient [36], and information about the disease is essential.…”
Section: Discussionmentioning
confidence: 99%
“…However, printed material on the disease and treatment is scarce, particularly in the low-volume centers, indicating that an important aspect of patient care is underappreciated [34,35]. Most recurrences are detected by the patient [36], and information about the disease is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that women tend to talk with people of similar experiences who have been able to overcome their illness crisis (18). Meeting like-minded people is a relief and reassurance for the individual and can make her learn adaptive methods to overcome the difficulties (19).…”
Section: Introductionmentioning
confidence: 99%
“…Despite widespread use and positive participant perceptions [33], only two RCTs testing one-to-one telephone peer support have been identified in the cancer literature [37,38]. Rudy and colleagues found that perceived social support was higher among melanoma patients receiving telephone peer support [38].…”
Section: Introductionmentioning
confidence: 99%
“…Rudy and colleagues found that perceived social support was higher among melanoma patients receiving telephone peer support [38]. The second study reported no significant difference in newly diagnosed GC patient’s emotional distress with peer telephone support, however the sample size was small ( n =32) [37].…”
Section: Introductionmentioning
confidence: 99%